Effects of mandibular protraction appliance associated to fixed appliance in adults - Bruno D'Aurea Furquim; José Fernando Castanha Henriques; Guilherme Janson; Danilo Furquim Siqueira; Laurindo Zanco Furquim (Dental Press Editora, 2013)
OBJECTIVE: This retrospective study aimed to conduct a cephalometric evaluation of the skeletal, dental and soft tissue effects resulting from treatment of adult patients presenting Class II malocclusion, performed with a Mandibular Protraction Appliance (MPA) combined with a fixed orthodontic appliance. METHODS: The sample consisted of teleradiographs obtained before and after treatment of 9 adult patients (initial mean age of 22.48 years) with bilateral Class II, division 1, malocclusion. Paired t test (p < 0.05) was applied to compare initial and final values. RESULTS: t test revealed an increase in anteroinferior facial height and posterior facial height. The dental changes include: extrusion of upper incisors, buccal inclination, protrusion of lower incisors, mesialization and extrusion of mandibular molars. Regarding the soft tissue component, there was an increase in nasolabial angle in addition to upper lip retrusion. CONCLUSIONS: The effects of treating Class II malocclusion adult patients, by means of using Mandibular Protraction Appliance (MPA) combined with a fixed appliance were mostly observed in the mandibular arch, and consisted of buccal inclination, protrusion and intrusion of incisors, and mesialization and extrusion of the molars.